Exploring the Raspberry Pi 2 with C++ - Gay, Warren (Apress : Imprint: Apress, 2015)
You have a Pi 2, but what exactly can you do with it? This book takes you on a tour of the Pi 2 hardware and all of the fantastic things that you can do to create innovative and useful projects with your Pi. Start with creating a workstation that does actual work, and move into installing a custom kernel, creating a clock, learning the ins and outs of the GPIO interface, and pick up some useful C++ skills along the way. Warren Gay, author of Mastering the Raspberry Pi, takes you through a set of experiments to show just what the Pi 2 is capable of and how you can use it to make your own fantastic creations. What You Will Learn: How to create an experimenter's workstation for the Pi 2, complete with breadboard and even Arduino All the details of GPIO, including a custom command for working with it Useful projects like a general purpose clock and the PiSpy Quick intro to C++ for the Pi How to make a multi-core webserver Who this book is for: Intermediate electronics enthusiasts and Pi fans, makers, students, teachers, and everyone who wants to know how to make the Pi really work.